IbM Kelompok Ibu-Ibu Rumah Tangga Pengolah Hasil Rumput Laut di Kabupaten Bantaeng - Asmidar, Asmidar; Asni, Andi; Hamsiah, Hamsiah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
Seaweed is one of the main commodities fisheries revitalization program that is expected to play an importantrole in improving the welfare of society. This service activities aimed at delivering a new innovation in the development ofseaweed processing activities . In achieving that goal then do some activities such as outreach to mothers and younghouseholds by introducing the equipment used , materials and demonstrations of new recipes from some modificationstoeaweed products in general, people in this area is still lacking utilizing processed seaweed products as food is ready toeat. Methods of approach are offered to support science and technology programs for the community is a participatorymethod in which partners are directly involved in the implementation of activities from preparation throughimplementation of these activities .The shape of the activityis met through discussion ( question and answer , lecture ),Deliberation , Focus Group Discussion ( FGD ) , workshops , demonstrations , publications and reinforcement. Types ofoutputs produced is in the form of modern products with specifications like lunkhead seaweed , cheese and crackers paperfish nuggets in the mix with seaweed can be a domestic industry products ( home industry ).  The results achieved in thisactivity is the formation of partners of seaweed processing group, namely sea and sunshine each consisting of 10 peopleeach group, the creation of employment where the mother-thousand households that used to be just as seaweed tieworkers become more creative and productive, Introducing processed products of modern seaweed creations fromcommunity service team that is cheese paper crackers and dodol seaweed